Efficient Cloud Server Job Scheduling using NN and ABC in cloud computing (International Journal of Engineering and Computer Science, 2018)
High work load not only translates to high operational cost, which reduces the marginal profit of Cloud-providers, which also direct towards low throughput of system. Henceforth, efficient job execution solutions are required to minimize the impact of Cloud computing on the environment. So, to generate such solutions, deep analysis of Cloud is obligatory with regard to their job-efficiency. Otherwise, Cloud computing with progressively persistent front-end client-devices interrelating with back-end data centers will cause an enormous load of jobs. To address this problem, data centre servers need to be managed in an efficient manner to drive computing.  In proposed work, hybrid algorithm which is based on neural network with artificial bee colony and some concepts of scheduling has been introduced in work. On the basis of them, tasks execution will be enhanced and load will be reduced. The results evaluation will be done on the basis of total jobs completed in the MATLAB 2010a environment.